A Compendium of Magnetic Nanoparticle Essentials: A Comprehensive Guide for Beginners and Experts - Carlos O. Amorim (Pharmaceutics)
Magnetic nanoparticles (MNPs) are advanced materials that combine the unique properties of magnetic materials and nanoscale dimensions, enabling a wide range of applications in biomedicine, environmental science, and information technology. This review provides a comprehensive yet accessible introduction to the fundamental principles, characterization techniques, and diverse applications of MNPs, with a focus on their nanoscale magnetic properties, such as superparamagnetism, single-domain behavior, and surface effects. It also delves into their classification and the critical role of parameters like magnetic anisotropy and blocking temperature. Emphasis is placed on routine characterization methods, including X-ray diffraction, electron microscopy, and magnetometry, as well as advanced concepts like magnetic hyperthermia and self-regulated heating. Designed for newcomers and experts alike, this review serves as both an educational guide and a quick-reference resource, ensuring clarity while maintaining scientific rigor.